2016
DOI: 10.1371/journal.pone.0164127
|View full text |Cite
|
Sign up to set email alerts
|

Association of Overweight with Food Portion Size among Adults of São Paulo – Brazil

Abstract: BackgroundAlthough studies show that portion size affects energy intake, few have demonstrated a link between portion size and weight status, especially in free-living populations. The objective of the present study was to assess the relationship between food portion sizes and overweight in a representative population of adults of São Paulo, Brazil.MethodsCross-sectional population-based study with 1005 adults from São Paulo, Brazil. Dietary data were obtained from two 24-hour recalls. Reported foods were clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Soft drinks and alcoholic beverages were the only groups that showed a positive association with excess weight in this study. The effect of the soft drink portion on excess weight has also been evidenced in the study by Pereira et al 13 in the adult population of the city of São Paulo (OR = 1.016, 95%CI 1.004–1.028), but the authors emphasize that the portion size of other high energy food, such as pizza, red meat, and snacks, also contributes with excessive weight gain.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Soft drinks and alcoholic beverages were the only groups that showed a positive association with excess weight in this study. The effect of the soft drink portion on excess weight has also been evidenced in the study by Pereira et al 13 in the adult population of the city of São Paulo (OR = 1.016, 95%CI 1.004–1.028), but the authors emphasize that the portion size of other high energy food, such as pizza, red meat, and snacks, also contributes with excessive weight gain.…”
Section: Discussionmentioning
confidence: 67%
“…In Brazil, only one study has evaluated the food portion sizes consumed, in a sample of adults of the city of São Paulo. The authors have found that large food portions from some groups with different energy densities, such as pizza, red meat, rice, snack foods, and soft drinks, are positively associated with excess weight 13 . However, there are no national studies that have estimated the beverage portion size consumed in a representative sample of the country and its relationship with excess weight.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, with 1005 adults from São Paulo in 2008, we observed a positive association between EBW and portion sizes of five food groupings: pizza, red meat, rice, salted snacks, and soft drinks [ 20 ]. In the present study, with larger sample size ( n = 5270) and broader age range (12 years and older), we confirmed the previous associations, and observed additional food groupings: cold cuts, fried snacks, fruit and commercial juices, soups, and sugar.…”
Section: Discussionmentioning
confidence: 99%
“…Foods and mixed dishes (such as feijoada, yakssoba and risotto) consumed by less than 5% of the population were not organized for grouping due to the low prevalence and high variability of nutritional values. Details of food grouping are reported in a previous ISA-Nutrition study by Pereira et al [ 20 ] and the list of foods that were included in each food grouping is described in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation